Gasoline Consumption and Cities Revisited: What have we learnt? - Newman, Peter; Kenworthy, Jeffrey (Scientific Research, 2021)
This article provides a personal reflection 30 years after we created the concept of automobile dependence. The paper entitled “Gasoline Consumption and Cities: A Comparison of US Cities with a Global Survey and Its Implications” and an associated book “Cities and Automobile Dependence” stirred up transport planning, especially in the US. We examine the criticisms, this evoked at the time within the perspective of what has happened in cities since then. Key policy prescriptions of re-urbanizing cities and prioritizing transit, walking and cycling, have been largely mainstreamed, though not without some painful changes in professional practice such as road capacity increases being seen as the only solution to traffic. Urban planning and transport policies adopted in innumerable cities worldwide have moved to reduce automobile dependence, though academic and policy debate continues. The future is likely to continue this debate, especially over autonomous cars where there will remain a fundamental need to keep cities on a path of reduced automobile dependence by ensuring that hard-won principles of re-urbanization of corridors, integrated with new transit alternatives and walkability at precincts/stations, are given the highest priority.